Challenges in secondary school education: profile of physics students' critical thinking skills - Marisda, Dewi Hikmah; Nurlina, Nurlina; Maruf, Maruf; Rahmawati, Rahmawati; Idamayanti, Reski; Akbar, Muhammad (Journal of Education and Learning (EduLearn), 2024)
For students to be able to compete and overcome challenges in the future, critical thinking is essential. The study’s descriptive methodology aims to describe the students’ critical thinking abilities. Every high school in a South Sulawesi district made up the research population. Based on school accreditation, with the use of a proportionate stratified random sampling technique, 150 students were chosen to comprise the research sample. The test instrument used is an essay distributed online. The indicators for the description questions are interpretation, analysis, and interpretation thinking skills. According to the study’s findings, students’ critical thinking abilities in static fluid material have an average score in the medium category of 73.09. In terms of school accreditation, students' physics critical thinking abilities average 73.87 for schools with A accreditation, 72.43 for schools with B accreditation, and 68.47 for schools with C accreditation. The percentage of each indicator of critical thinking skills is 34.58 in inference, 33.70 in analysis, and 31.71 in interpretation. It is anticipated that this study will give a broad picture of students’ critical thinking competencies for teachers to choose and implement the most suitable stimulus to aid students in developing their critical thinking abilities.